Peran Mahasiswa dalam Pencegahan Perdagangan Orang (Human Traffciking) di Daerah Cikarang - Trias Saputra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Trafficking in persons (human trafficking) is an act that is contrary to human dignity and human dignity and a crime that violates human dignity and rights to the detriment of individuals, society and the state. These crimes are latent and are often surrounded by a lack of understanding about the aspects involved and how to distinguish them from other forms of violence. In Indonesia, men, women and children are victims of human trafficking with the aim of labor exploitation and sexual exploitation, exploitation as beggars and criminals who make profits for recruiters and traffickers. as students, lecturers and students have an understanding of the forms and efforts to prevent trafficking in persons, especially in the campus area, namely Cikarang in the form of legal counseling. It is hoped that students will become agents of prevention and assistance in the event of human trafficking